Problem solved! - Thomas, Jan, 1958- (Beach Lane Books, 2023)
"Rabbit has a problem! Her room is a mess. Luckily, Pete the Problem-Solving Porcupine shows up just in time. He can save the day! Except...things don't go quite to plan, and Rabbit realizes that Pete may actually be a problem-causer! Can Rabbit find a way to solve this unexpected new dilemma before chaos ensues?" --